1997
DOI: 10.1080/00986449708936599
|View full text |Cite
|
Sign up to set email alerts
|

Forced Convection Mass Transfer Inside Large Hemispherical Cavities Under Laminar Flow Conditions

Abstract: Rates of mass transfer at hemispherical cavities machined in the wall of a vertical rectangular duct were measured by an electrochemical technique which involved measuring the limiting current of the cathodic reduction of K 3 Fe(CN), . Variables studied were solution flow rate, physical properties of the solution and cavity diameter. The mass transfer coefficient inside the cavity was found to be less than the flat surfaoe value (the duct wall), and decreased with an increase in the cavity diameter. Mass trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Levich and Agar first proposed this system to investigate the heat transfer, and Selman and Tobias developed the method further. Zaki et al reported the use of mass transfer experiments. Chung et al have also published a series of experimental results applying the methodology for various flow conditions and geometries.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Levich and Agar first proposed this system to investigate the heat transfer, and Selman and Tobias developed the method further. Zaki et al reported the use of mass transfer experiments. Chung et al have also published a series of experimental results applying the methodology for various flow conditions and geometries.…”
Section: Methodsmentioning
confidence: 99%
“…and Agar 19 first proposed this system to investigate the heat transfer, and Selman and Tobias 20 developed the method further. Zaki et al21 …”
mentioning
confidence: 99%